Effectiveness and limitations of reconstruction of the medial patellofemoral ligament using a titanium interference screw in single patellar and femoral bone tunnels - Nobuyuki Kumahashi; Suguru Kuwata; Takahito Inoue; Yuji Uchio (Elsevier, 2014)
No standard surgical procedure for medial patellofemoral ligament (MPFL) reconstruction exists. The purpose of this study was to evaluate the clinical effectiveness and limitation of the reconstructions of the MPFL in single patellar and femoral bone tunnels. The methods used a hamstring tendon and titanium interference screws in patients with recurrent patellar dislocation. Nineteen knees in 17 patients were studied. Subjects underwent MPFL reconstruction with or without lateral release using interference screws in single patellar and femoral tunnels. Patients were evaluated using preoperative and postoperative physical and radiographic examinations, including apprehension testing, assessment of tilting and congruence angles, medial and lateral shift ratios under stress X-ray imaging, and Kujala and Lysholm scores. Average follow-up was 22 months (12-71 months). None experienced recurrent postoperative episodes of dislocation or subluxation. By the final follow-up, patellar apprehension had disappeared in all patients except for one with generalized joint laxity. In addition, patients showed significant improvement in the following areas: tilting angle (from 14.4 ± 5.6° to 6.4 ± 4.6°, p < 0.0001), congruence angle (0.5 ± 16° to −9.2 ± 6.9°, p < 0.001), lateral shift ratio (23.8 ± 11.3% to 11.6 ± 13.4%, p < 0.001), Kujala score (74.0 ± 7.8 points to 95.7 ± 4.4 points, p < 0.0001), and Lysholm score (71.0 ± 10 points to 95.5 ± 5.3 points, p < 0.0001). MPFL reconstruction methods, using titanium interference screws in single patellar and femoral tunnels provide acceptable short-term results for the treatment of recurrent patellar dislocations.